Isolation, purification and characterization of natural red pigment from dragon fruit (hylocereus polyrhizus) / Ow Rebecca Phui San - Ow, Rebecca Phui San (2012)
Stability, antioxidant properties, toxicology profile of betacyanins and selected target genes from Hylocereus polyrhizus were studied. In the stability study, the pigments were obtained using water extraction and juice concentration; extracted at room temperature (RT) and 100ºC; and stored under -20ºC, 4ºC and RT. In the water extraction method, the best weight: volume ratio was obtained using the ratio of 1:1. Pigments extracted at RT and from juice concentrate showed lower total betalain concentration changes as compared to samples extracted at 100ºC and from water extraction. Pigments stored at -20ºC under both extraction methods showed minimal change compared to those stored at RT and 4ºC. Analysis using the High Performance Liquid Chromatography (HPLC) confirmed the presence of betanin. Total polyphenol assay showed that there were 86.10mg of total polyphenolic compound in 0.50g of dried extract and this was further confirmed by thereducing power assay which showed an increase in the reducing capability from 0.18 to 2.37. The Vanillin-HCl assay which measures the amount of condensed tannin showed that the dried dragon fruit sample had an equivalent of 2.30mg catechin/g while the DPPH• radical scavenging activity determination showed that the effective concentration (EC50) for dragon fruit was 2.90 vitamin C equivalents/g dried extract. X-ray crystallography, High Performance Liquid Chromatography (HPLC), Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) and Nuclear Magnetic Resonance (NMR) yielded a novel discovery of myo-inositol crystals. The purity level of crystals was verified using HPLC where a clean single peak was obtained, while LC-MS/MSwas employed to provide a comparison with myo-inositol standard. NMR established the molecular structure and conformation of the crystals. This is the first time myo-inositol crystals were isolated and reported for Hylocereus polyrhizus.